PENERAPAN STRATEGI KONFLIK KOGNITIF UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP - Asep Sujana; Rusdian Rifa'i; Nurfuji Astuti (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2019)
This study aims to determine the improvement of mathematical critical thinking skills of class VIII students of SMP Negeri 2 Saketi through cognitive conflict strategies. This study uses a quasi-experimental method that design pretest-posttest control group and determining the sample in this study using cluster random sampling technique with class VIII A as many as 25 students as the experimental class and class VIII B as many as 25 students as the control class. Based on data analysis and hypothesis testing, it can be concluded that cognitive conflict strategies can improve mathematical critical thinking skills of eighth grade students of Saketi State Middle School 2. Keywords: Cognitive Conflict Strategy, Mathematical Critical Thinking